Perhitungan Komposisi Dan Evaluasi Pengelolaan Sampah 3R Di Kampus 3 Universitas Pgri Semarang - Universitas PGRI Semarang, Velma Nindita Arsitektur, (Teknis, 2017)
The present for green campus in University of PGRI Semarang is not only emphasizing on greening the campus, but also green living lifestyle that is green in everyday life. The concept of recycling for garbage which commonly referred as the 3Rs (Reduce, Reuse, Recycle) is solution that can be considered, so that the economic value contained in garbage can be utilized. This study aims to analyze the volume and composition of waste from the existing condition of the operational techniques of waste management to optimize its development prospects through an action plan on the campus of the University of PGRI 3, Bendan Duwur Semarang. Data collection methods used were interview, observation and simple random sampling. The data is analyzed qualitative descriptively. The results showed that the calculation of the average volume of waste resulting from activities that occur on campus 3 Bendan Duwur UPGRIS is mostly obtained as much as 88% category leaves, twigs litter composition of 4.5%, 4.45% waste paper and plastic waste 2.51%. Largely organic waste, because at this location there are many teak trees. The amount of inorganic waste is very small because that place is not exclusively used for all lectures, but it mostly used for laboratory activities. From the analysis, it will be designed an action plan for waste management on campus 3 Bendan Duwur PGRI University, including the separation process waste from its source, measurement of waste generation and waste composition continuously, design of technology for the processing of organic waste appropriately therefore produce economic value product.Keyword : garbage, 3R, generation volume, the action plan.